Quantitation of Intracellular Triphosphate of Emtricitabine in Peripheral Blood Mononuclear Cells from Human Immunodeficiency Virus-Infected Patients - Darque, Albert (American Society for Microbiology, 1999)
An analytical methodology combining solid-phase extraction (SPE) and high-performance liquid chromatography (HPLC) was developed to quantitate the intracellular active 5′-triphosphate (TP) of β-l-2′,3′-dideoxy-5-fluoro-3′-thiacytidine (emtricitabine) (FTC) in human peripheral blood mononuclear cells (PBMCs). The FTC nucleotides, including 5′-mono-, di-, and triphosphates, were successively resolved on an anion-exchange SPE cartridge by applying a gradient of potassium chloride. The FTC-TP was subsequently digested to release the parent nucleoside that was finally analyzed by HPLC with UV detection (HPLC-UV). Validation of the methodology was performed by using PBMCs from healthy donors exposed to an isotopic solution of [(3)H]FTC with known specific activity, leading to the formation of intracellular FTC-TP that was quantitated by an anion-exchange HPLC method with radioactive detection. These levels of FTC-TP served as reference values and were used to validate the data obtained by HPLC-UV. The assay had a limit of quantitation of 4.0 pmol of FTC-TP (amount on column from approximately 10(7) cells). Intra-assay precision (coefficient of variation percentage of repeated measurement) and accuracy (percentage deviation of the nominal reference value), estimated by using quality control samples at 16.2, 60.7, and 121.5 pmol, ranged from 1.3 to 3.3% and −1.0 to 4.8%, respectively. Interassay precision and accuracy varied from 3.0 to 10.2% and from 2.5 to 6.7%, respectively. This methodology was successfully applied to the determination of FTC-TP in PBMCs of patients infected with human immunodeficiency virus after oral administration of various dosing regimens of FTC monotherapy.